Midwives Knowledge Level Survey On Ultra Process Food (UPF) On Childrens Complementary Feeding Practices: An Explanatory Study - Kusmayra Ambarwati (International Journal of Medicine and Health, 2023)
Proper complementary nutrition is critical for child growth. Currently, UPF consumption is common, affecting IYCFP, where many older persons use CCF. Indeed, CCF has a negative impact on children's growth and development. Many factors contribute to this, one of which is a lack of assistance from other health providers, especially midwives. In Indonesia, midwives are the primary health workers that offer direct care to mothers. According to several sources, midwives continue to provide little support in this area due to insufficient experience and expertise. The purpose of this study is to determine the level of awareness of UPF and ICYFP among midwives. The method employed is a hybrid strategy that employs successive explanation strategies. 114 midwives participated in the online study in 2022. The results of this study showed that there are still many midwives who do not know about UPF and IYCFP education and advocacy. There needs to be government support to conduct comprehensive education in the health sector, including midwives.